2016
DOI: 10.1021/acsami.5b12055
|View full text |Cite
|
Sign up to set email alerts
|

Doping Evolution and Junction Formation in Stacked Cyanine Dye Light-Emitting Electrochemical Cells

Abstract: Cyanine dyes are fluorescent organic salts with intrinsic conductivity for ionic and electronic charges. Recently ( J. Am. Chem. Soc. 2013 , 135 , 18008 - 18011 ), these features have been exploited in cyanine light-emitting electrochemical cells (LECs). Here, we demonstrate that stacked, constant-voltage driven trimethine cyanine LECs with various counteranions develop a p-i-n junction that is composed of p- and n-doped zones and an intrinsic region where light-emission occurs. We introduce a method that comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 57 publications
2
47
1
Order By: Relevance
“…A wide range of organic materials has been used in the manufacture of LECs. 7,8,9,10,11 However, the best efficiencies have been achieved with ionic transition-metal complexes (iTMCs), 12,13,14,15 and, in particular, with iridium(III) complexes due to their efficient spin-orbit coupling, which ideally allows to harvest 100% of the excitons generated in the device.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of organic materials has been used in the manufacture of LECs. 7,8,9,10,11 However, the best efficiencies have been achieved with ionic transition-metal complexes (iTMCs), 12,13,14,15 and, in particular, with iridium(III) complexes due to their efficient spin-orbit coupling, which ideally allows to harvest 100% of the excitons generated in the device.…”
Section: Introductionmentioning
confidence: 99%
“…LECs [12][13][14][15][16][17][18][19]. They are considered as an easy-to-purify [12] and low-cost [13] alternative to the more investigated polymer and iTMC materials.…”
Section: Recently Neutral and Ionic Small Molecules Have Been Employmentioning
confidence: 99%
“…The number of mobile charges within the intrinsic region at 10 mA cm -2 amounts to ~10 16 cm -3 assuming a charge carrier mobility of 10 -5 cm 2 V -1 s -1 [39] and an electric field across the intrinsic region of 70 V µm -1 . Using chemical doping of cyanine dyes it was shown that for a substantial PL quenching a doping concentration of some percentage is required [15].…”
Section: Lec Behaviormentioning
confidence: 99%
“…It should, however, be acknowledged that a vast majority of the subsequent research on iTMC-LECs have employed an additional electrolyte (often an ionic liquid) in order to attain a reasonably fast turn-on time [4,5]. The LEC field has up until now been dominated by these two principal classes of compounds, although new groups of functional materials, in the form of non-ionic luminescent small molecules [6][7][8][9][10][11][12][13][14], ionic fluorescent small molecules [15][16][17], quantum dots [18,19], and perovskites [20,21], have emerged more recently. Figure 1c presents the chemical structures of a CP, an iTMC, and a luminescent small molecule, as well as a number of electrolytes that have been utilized in recent high-performance LEC devices.…”
Section: Introductionmentioning
confidence: 99%